2017
DOI: 10.1002/mp.12265
|View full text |Cite
|
Sign up to set email alerts
|

Methodological accuracy of image-based electron density assessment using dual-energy computed tomography

Abstract: This is the pre-peer reviewed version of the article entitled "Methodological accuracy of image-based electron-density assessment using dual-energy computed tomography", which has been accepted for Purpose: Electron density is the most important tissue property influencing photon and ion dose distributions in radiotherapy patients. Dual-energy computed tomography (DECT) enables the determination of electron density by combining the information on photon attenuation obtained at two different tube voltages. Most… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…For the dense bone, the elemental composition data provided by the manufacturer indicated that there was a small percentage of Barium in the insert. The presence of this high-Z material may not be compatible with our DE calculations [10,19]. Given these potential complications with the phantom measurements, further investigations are warranted using phantoms from other manufacturers and/or organic materials taken from animal models.…”
Section: Discussionmentioning
confidence: 87%
“…For the dense bone, the elemental composition data provided by the manufacturer indicated that there was a small percentage of Barium in the insert. The presence of this high-Z material may not be compatible with our DE calculations [10,19]. Given these potential complications with the phantom measurements, further investigations are warranted using phantoms from other manufacturers and/or organic materials taken from animal models.…”
Section: Discussionmentioning
confidence: 87%
“…The recent letter by Dr. Saito refers to the theoretical framework of electron-density determination by dual-energy computed tomography (DECT), as presented in the appendix of our article. 1 After performing some calculations in this framework, the author of the Comment concludes that "the form of Eq. (A1) [.…”
mentioning
confidence: 99%
“…(A1). 1,5 Raising doubts about the applicability of Eq. (A1) would therefore reduce trust in the validity of Eq.…”
mentioning
confidence: 99%
“…To the Editor, I write this letter in reference to the recent paper by M€ ohler et al 1 In that study, the authors evaluated the methodological uncertainties of the dual-energy computed tomography (DECT) method for electron-density calculations with a single material-independent parameter a, which was developed by Saito. 2 Given the high accuracy and robustness of the simple method, the authors concluded that no further improvement is expected from more complex image-based DECT-algorithms for electron-density calculations.…”
mentioning
confidence: 99%
“…4 They have also given an alternative form of photon attenuation characterized by mixtures of two basis materials (e.g., water and bone), 5 which is currently preferred as a more practical method in DECT. In my previous study based on the two-basis material decomposition, 6 I have elucidated that the optimal a opt determined by a least squares fitting is equivalent to a weighting factor, which synthesizes a virtual monochromatic CT image acquired at 1 MeV [a 1 . At this energy, the photonmatter interaction for human tissues is exclusively Compton scattering, a process in which the photon attenuation is proportional to the electron density of the material but independent of its atomic number (i.e.,l l MeV ¼n).…”
mentioning
confidence: 99%